1997
DOI: 10.1093/schbul/23.4.583
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tardive Dyskinesia

Abstract: Although the new generation of atypical antipsychotic agents could some day eliminate concerns about tardive dyskinesia (TD), this disorder remains a significant clinical problem for both patients and physicians. Fortunately, many, if not most, cases of TD are mild. For patients with mild to moderate TD, therapeutic efforts are primarily directed at minimizing neuroleptic exposure or, when possible, changing to atypical agents. Most cases of TD do not seem to progress, suggesting that the risk of remaining on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 218 publications
3
91
0
2
Order By: Relevance
“…Neuroleptics are extensively used in the treatment of schizophrenia and other affective disorders. TD, which occurs in 20-40% of patients taking chronic neuroleptic medication, is a major limitation of neuroleptic therapy (Egan et al 1997;Casey 2000;Kulkarni and Naidu 2001). In spite of its high frequency of occurrence, the pathophysiology of tardive dyskinesia remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroleptics are extensively used in the treatment of schizophrenia and other affective disorders. TD, which occurs in 20-40% of patients taking chronic neuroleptic medication, is a major limitation of neuroleptic therapy (Egan et al 1997;Casey 2000;Kulkarni and Naidu 2001). In spite of its high frequency of occurrence, the pathophysiology of tardive dyskinesia remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Certain patientand treatment-related risk factors that increase the likelihood of developing TD have been identified (Box 3) [58,59]. How these factors confer vulnerability to TD remains largely unknown, and not all patients with these characteristics will develop TD.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Patient factors associated with TD include increased age, psychiatric diagnosis, female sex (particularly in elderly patients), diabetes, organic brain damage, development of other neurological side effects (e.g., extrapyramidal symptoms [EPS]), and the presence of negative symptoms of schizophrenia [59][60][61][62][63][64].…”
Section: Patient Factorsmentioning
confidence: 99%
“…9 In addition, genetic susceptibility contributes to individual susceptibility to develop TD following antipsychotic exposure, 10 and despite methodological difficulties, family studies support a genetic component. 11,12 The pathogenesis of TD is unknown and may involve supersensitivity of the nigrostriatal pathway dopamine D2 receptors, 13 neuronal damage caused by free radical overproduction 14,15 and GABAergic system dysregulation. 16,17 Interestingly, several studies have shown that spontaneous movement disorders, mainly spontaneous dyskinesia, may be present in antipsychotic-naive schizophrenia patients and may represent an intrinsic neuromotor component of this disorder.…”
Section: Introductionmentioning
confidence: 99%